Developmental Cascades of Internalizing and Externalizing Problems from Infancy to Middle Childhood: Longitudinal Associations with Bullying and Victimization. (3rd July 2022) - D'Urso, Giulio; Symonds, Jennifer
ABSTRACT: The current study investigates how internalizing and externalizing problems develop reciprocally across infancy to middle childhood, in relation to children's gender, cognitive functioning, socioeconomic status, and parental stress. The study also examines the impact of the developmental cascade of internalizing and externalizing problems on bullying and victimization in middle childhood. The total sample comprised 11, 134 participants studied across 9-months, 3-years, 5-years, 7/8-years and 9-years of age, from the Infant Cohort of the Growing Up in Ireland study (50.6% male). Using structural equation modeling, we discovered that externalizing problems predicted internalizing problems across time for both genders. However, internalizing problems predicted externalizing problems consistently across time for girls and not for boys. Furthermore, girls' internalizing and externalizing problems were much more strongly predicted by socioeconomic status than boys' problems were, suggesting a greater sensitivity to context for girls. Bullying in middle childhood was predicted by cognitive ability for both genders, and by externalizing problems for boys. In comparison, victimization was predicted by externalizing and internalizing problems for both genders. Theoretical and practical implications are discussed.